Pengabdian dalam Upaya Pencapaian Kondisi Permukiman, Sarana, dan Prasarana Sehat Dalam Mewujudkan Kabupaten Banyuwangi Sehat di Tahun 2021 - Nur Anim Jauhariyah; Soekardjo Soekardjo; Pipit Hariyono (IAI Darussalam, 2021)
This service in efforts to achieve healthy housing conditions, facilities and infrastructure in realizing a Healthy Banyuwangi Regency is carried out as an effort to maintain environmental comfort and health, including reforestation activities by planting trees and protecting rivers from pollution. The data shows that the number of trees planted from 2013 to 2020 is 7,774,132. Although the Covid-19 pandemic still haunts people's lives, activities in an effort to improve the quality of proper air and water continue to carry out health protocols.